2002
DOI: 10.1046/j.0306-5251.2001.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized cross‐over clinical trial to study potential pharmacokinetic interactions between cisplatin or carboplatin and etoposide

Abstract: Aims Cisplatin and carboplatin are often used in combination with etoposide. In a randomized cross-over study, the potential interaction between the two platinum drugs and the metabolism of etoposide was explored. In vitro investigations using human liver microsomes were also performed. Methods Etoposide was administered to 15 patients over 3 days, with the platinum drug administered on day 2. The alternate platinum drug was administered on the second course. The pharmacokinetics of etoposide were determined o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The systemic exposure to etoposide found in our study is comparable to earlier findings. Thomas and colleagues observed an AUC 0–24h of 85 mg/L*hour to etoposide after a dose of 100 mg/m 2 , which is in line with the AUC 0–24h of 83.7–86.2 mg/L*hour, as reported in our study after an equal dose 20 . Based on dose‐proportional pharmacokinetics of etoposide over a dose range of 100–600 mg/m 2 , it is not expected that a different effect will be observed at other dose levels 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The systemic exposure to etoposide found in our study is comparable to earlier findings. Thomas and colleagues observed an AUC 0–24h of 85 mg/L*hour to etoposide after a dose of 100 mg/m 2 , which is in line with the AUC 0–24h of 83.7–86.2 mg/L*hour, as reported in our study after an equal dose 20 . Based on dose‐proportional pharmacokinetics of etoposide over a dose range of 100–600 mg/m 2 , it is not expected that a different effect will be observed at other dose levels 21 .…”
Section: Discussionsupporting
confidence: 93%
“…Geometric means and the geometric mean ratio (GMR) of exposure over time (AUC 0–24h ) of etoposide with and without aprepitant was calculated. When the 90% confidence interval (CI) of the GMR falls within the 0.8–1.25 limits, this interaction is considered non‐clinically relevant in line with the FDA guideline “Clinical Drug Interaction studies – Cytochrome P450 enzyme‐ and transporter‐mediated drug interactions guidance for industry” 20 . Pharmacokinetic parameters and descriptive statistics were performed by noncompartmental analysis using Phoenix WinNonlin 8.3.4.295.…”
Section: Methodsmentioning
confidence: 99%
“…However, tamoxifen did not alter the pharmacokinetics of etoposide in patients with hepatocellular carcinoma [254]. Cisplatin or carboplatin only had a minor effect on the pharmacokinetics of etoposide in cancer patients [255].…”
Section: Etoposide + Grapefruit Juicementioning
confidence: 98%
“…There are two studies that have reported no pharmacokinetic interaction between carboplatin and etoposide [33,34], and one study has reported an interaction between melphalan and carboplatin [35]. As these drugs were coadministered in all patients in the present study, potential drug-drug interactions could not be investigated directly.…”
Section: Limitationsmentioning
confidence: 81%